2022
DOI: 10.1108/ribs-12-2021-0178
|View full text |Cite
|
Sign up to set email alerts
|

Small and medium enterprises dynamic capabilities efficacy during COVID-19: moderating role of CEO gender

Abstract: Purpose This study aims to investigate the role of dynamic capabilities (DCs) in the financial performance of the small and medium enterprises (SMEs) during COVID-19. Furthermore, it took chief executive officer gender to moderate the relationship between DCs and financial performance. Design/methodology/approach This study used the survey approach to collect the data. Regression analysis was used on 563 responses to test the proposed hypotheses. Findings The results showed that DCs have a significant posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…During the pandemic, central banks took proactive steps by implementing monetary stimulus policies to alleviate concerns regarding the solvency and liquidity of non-financial companies. Numerous countries have introduced loan guarantee programs and credit support measures aimed at providing assistance to businesses [ 67 , 68 ]. These measures, particularly those related to loan guarantees and the government's acquisition of corporate bonds, infused much-needed liquidity into companies [ 69 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…During the pandemic, central banks took proactive steps by implementing monetary stimulus policies to alleviate concerns regarding the solvency and liquidity of non-financial companies. Numerous countries have introduced loan guarantee programs and credit support measures aimed at providing assistance to businesses [ 67 , 68 ]. These measures, particularly those related to loan guarantees and the government's acquisition of corporate bonds, infused much-needed liquidity into companies [ 69 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Temporal aspects are especially inherent to grand challenges, as they involve multiple time frames (Ferraro et al, 2015), imply a trade-off of todays' consumption and future generation's needs (Brundtland, 1987), and require actions today that will only materialize in the future. Given this temporal aspect of grand challenges on the one hand, and the outstanding role of Chief Executive Officer (CEO) as chief cognizer (Nadkarni and Chen, 2014) and decision-making authority (Ahmad et al, 2023;Ali et al, 2022;Naseem et al, 2020) that have been shown to play a vital role in explaining the variety of environmental responses (Lewis et al, 2014) on the other hand, we expect CEOs' orientation towards time to affect firms' awareness and hence identification of grand challenges as well as their subsequent interpretation. We utilize the example of water scarcity as a grand challenge and investigate the relationship between CEOs' temporal focus and firms' identification and interpretation of the grand challenge as an opportunity.…”
Section: Introductionmentioning
confidence: 99%